Hostility and Violence as Consequences of Turbulent Partition in Khushvant Singh’s Train to Pakistan - Solanki, Milind Kantilal; Ratad, Pratap B. (International Journal of English Literature and Social Sciences (IJELS), 2019)
The present paper is an attempt to study the violence and hostility in Khushwant Singh’s Train to Pakistan. To achieve the aim of the study, the violence and hostility which emerged from the partition of British India are evaluated by the parameters: Sikhs and Muslims, India and Pakistan, People and Government, Men and Women, and Peace and Conflict. How the partition affects the people of Mano-Majra? This has been evaluated through these parameters of the study. Here the study is an attempt to explore the consequences which affected the people of both side of the borders; India and Pakistan. The rise of violence and hostility among the dwellers of Mano-Majra, the neighbors of centuries are affected due to this phenomena. Partition shook their roots of togetherness and created fear and anxiety. At the end they got nothing except suffering, human and property lose, woman were raped and shattered their faith against violence and hostility prevailing everywhere in the crisis of identity, individuality and liberty. What factors lead the consequences primarily hostility and violence, have elaborated in the paper.